Content validity of symptom‐based measures for diabetic, chemotherapy, and HIV peripheral neuropathy. Issue 3 (23rd December 2016) - Gewandter, Jennifer S.; Burke, Laurie; Cavaletti, Guido; Dworkin, Robert H.; Gibbons, Christopher; Gover, Tony D.; Herrmann, David N.; Mcarthur, Justin C.; McDermott, Michael P.; Rappaport, Bob A.; Reeve, Bryce B.; Russell, James W.; et al.
ABSTRACT: Introduction : No treatments for axonal peripheral neuropathy are approved by the United States Food and Drug Administration (FDA). Although patient‐ and clinician‐reported outcomes are central to evaluating neuropathy symptoms, they can be difficult to assess accurately. The inability to identify efficacious treatments for peripheral neuropathies could be due to invalid or inadequate outcome measures. Methods : This systematic review examined the content validity of symptom‐based measures of diabetic peripheral neuropathy, HIV neuropathy, and chemotherapy‐induced peripheral neuropathy. Results : Use of all FDA‐recommended methods to establish content validity was only reported for 2 of 18 measures. Multiple sensory and motor symptoms were included in measures for all 3 conditions; these included numbness, tingling, pain, allodynia, difficulty walking, and cramping. Autonomic symptoms were less frequently included. Conclusions : Given significant overlap in symptoms between neuropathy etiologies, a measure with content validity for multiple neuropathies with supplemental disease‐specific modules could be of great value in the development of disease‐modifying treatments for peripheral neuropathies. Muscle Nerve 55 : 366–372, 2017